The Exploitation of Religious Narratives: The Study of “Jihad Nikah” Narratives in the ISIS Al-Qur'an Perspective: Eksploitasi Narasi Keagamaan: Studi Tentang Narasi “Jihad Nikah” pada ISIS Perspektif Al-Qur'an - Haris Fatwa Dinal Maula (Jurnal Dialog, 2021)
ISIS uses the term “marriage jihad” narrative to attract new recruits, especially among women. Although ISIS was declared defeated in 2016, the seeds of the “jihadi brides” narrative can still be found in some acts of terrorism around the world even today. Hence, the study of “marriage jihad” is seen very relevant and urgent to be conducted. “Marriage jihad” narrative, according to them, emphasizes the importance of expecting mothers who will deliver warriors and soldiers who involved in their holy war. On the other hand, this narrative is also used to legitimize biological motives of ISIS combatants. Based on human rights perspective, this narrative is the kind of women slavery who are perceived as sexual objects. This is often wrapped in religious terminology, such “for the sake of Islam”. The “marriage jihad” phrase, which has never been found in the history of Islamic discourse, is analyzed through the perspectives of the Qur’an based on Ma’na Cum Maghza approach. According to the Qur’anic perspectives, both jihad and marriage have the same goal, that is to build a vision of peace and compassion. So the narrative of the “marriage jihad” initiated by ISIS is certainly at odd with the Islamic principles. ISIS menggunakan narasi “jihad nikah” untuk menarik calon anggota baru, khususnya perempuan. Meskipun ISIS telah dinyatakan kalah pada tahun 2016, benih-benih narasi “jihadi brides” masih dapat ditemukan dalam berbagai aksi terorisme di seluruh dunia hingga saat ini. Kondisi tersebut menjadikan kajian mengenai narasi “jihad nikah” tetap relevan dan urgen untuk dilakukan. Artikel ini membahas eksploitasi terminologi agama dalam agenda propaganda ISIS melalui konsep “jihad nikah”. Narasi ini, menurut mereka, menekankan pentingnya perempuan untuk dihamili agar anak-anak yang lahir kelak menjadi pejuang dan prajurit yang memperjuangkan tujuan mereka. Di sisi lain, narasi tersebut juga digunakan sebagai legitimasi bagi pemenuhan kebutuhan syahwat para kombatan ISIS yang berada di medan perang. Frasa “jihad nikah” sendiri tidak pernah ditemukan dalam sejarah diskursus Islam. Tulisan ini mengupas narasi “jihad nikah” dalam perspektif al-Qur’an dengan menggunakan pendekatan Ma’na Cum Maghza. Menurut sudut pandang tafsir al-Qur’an, jihad dan nikah memiliki tujuan yang serupa, yaitu membangun visi perdamaian yang berlandaskan kasih sayang. Oleh karena itu, narasi “jihad nikah” yang diprakarsai oleh ISIS tersebut jelas bertolak belakang dengan prinsip-prinsip Islam.